HUBUNGAN TINGKAT STRES, POLA KONSUMSI DAN AKTIVITAS FISIK DENGAN SIKLUS MENSTRUASI PADA REMAJA PUTRI DI WILAYAH KERJA PUSKESMAS KENALI BESAR TAHUN 2024 - Oktalia, Viqkha Putri; Ibnu, Ismi Nurwaqiah; Perdana, Silvia Mawarti (STIKes Mitra Keluarga, 2024)
Introduction : A regular menstrual cycle lasts 21-35 days and the duration of menstruation ranges from 3-7 days. The prevalence of irregular menstrual cycles in Indonesia regarding menstrual irregularities shows 11.7% and in Jambi Province, 17.1% of teenagers aged 15 - 18 years experience menstrual cycle irregularities, influenced by many factors. This study aims to determine the relationship between stress levels, consumption patterns and physical activity with the menstrual cycle of adolescent girls in the Kenali Besar health center working area, Jambi City. Method: This research design is cross sectional with an analytical observational approach with a sample size of 92 respondents using proportional sampling techniques. This research variable includes stress levels, consumption patterns, physical activity and menstrual cycle. Data analysis used the chi-square test. Result: There is a relationship between stress levels (p-value = 0.003) with PR 1.709 (95%CI 1.203 – 2.428) and consumption patterns (p-value = < 0.001) PR 2.44 (95%CI 1.509 – 3.757) on the menstrual cycle irregular and there is no relationship with the physical activity variable (p-value = 0.318) PR 0.813 (95%CI 0.573 –1.155). Conclusion: There is a relationship between stress levels and consumption patterns and the menstrual cycle of adolescent girls. No relationship was found between physical activity and the menstrual cycle. It is hoped that young women will understand how to manage stress well, this can be done by arranging a balanced daily diet and adequate nutritional intake.